2009
DOI: 10.1093/rheumatology/kep270
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events and efficacy of TNF-  blockade with infliximab in patients with systemic lupus erythematosus: long-term follow-up of 13 patients

Abstract: Short-term therapy with four infusions of infliximab in combination with AZA was relatively safe, and had remarkable long-term efficacy for lupus nephritis and, potentially, also interstitial lung disease. Long-term therapy with infliximab, however, was associated with severe adverse events in two out of three SLE patients, which may have been provoked by infliximab and/or by their long-standing refractory SLE and previous therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
9

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(113 citation statements)
references
References 19 publications
2
102
0
9
Order By: Relevance
“…Finally, in patients with lupus nephritis, 10 weeks of infliximab treatment reduced proteinuria but increased anti-DNA antibodies. Longer treatment was associated with adverse effects (68). In patients with RA treated with anti-TNF-a mAbs, lupus syndromes developed, anti-DNAs were induced (69), and some patients developed GN (70).…”
Section: Autoimmune Crescentic Glomerulonephritis Lupus Nephritismentioning
confidence: 99%
“…Finally, in patients with lupus nephritis, 10 weeks of infliximab treatment reduced proteinuria but increased anti-DNA antibodies. Longer treatment was associated with adverse effects (68). In patients with RA treated with anti-TNF-a mAbs, lupus syndromes developed, anti-DNAs were induced (69), and some patients developed GN (70).…”
Section: Autoimmune Crescentic Glomerulonephritis Lupus Nephritismentioning
confidence: 99%
“…There is little evidence for the severity of LP in immunosuppressed patients, although one study following up patients with systemic lupus erythematosus taking infliximab reported a death secondary to LP. 25 However, only a small number in our series were im-munosuppressed or had chronic kidney disease.…”
Section: Diagnosis and Treatmentmentioning
confidence: 70%
“…Pro-inflammatory cytokines IL-1β and TNF-α were reduced following treatment with FK228 [89]. TNF-α is known to play an important role in the pathogenesis of a number of autoimmune diseases including SLE, RA, and Crohn's disease and anti-TNF-α therapies have proven to be an effective clinical treatment for people with these diseases [38, [90][91][92][93]. The molecular mechanism through which FK288 reduces inflammation has yet to be determined.…”
Section: Selective Class I Inhibitorsmentioning
confidence: 99%